Sleep trajectories and osteoporosis incidence: findings from two prospective cohort studies - Zhang, Xiangxiang; Li, Zongshan; Tian, Huanyong; Lv, Tian; Shang, JinXiang; Cai, Ermin (Frontiers in Public Health, 2025)
BackgroundMost studies evaluate sleep quality at a single time point, and few have employed repeated measurements to investigate this association. This longitudinal research investigated changes in sleep quality patterns among older adults and examined their relationship with the onset of osteoporosis.MethodsWe analyzed data from two prospective cohorts: Participants comprised 4,328 individuals from the English Longitudinal Study of Aging (ELSA) and 9,132 from the U.S. Health and Retirement Study (HRS). Sleep quality was quantified using standardized sleep quality scores, and trajectories were determined based on baseline and follow-up assessments. Changes in sleep quality status were categorized to reflect persistent, improving, or deteriorating patterns. Associations between sleep quality trajectories and osteoporosis incidence were examined using Cox proportional hazards regression models.ResultsAt baseline, sleep quality was significantly associated with the prevalence of osteoporosis in both datasets (ELSA: HR = 1.11, 95% CI: 1.08–1.15; HRS: HR = 1.1, 95% CI: 1.07–1.13). During the follow-up period, compared with participants with persistently good sleep quality, those with persistently poor sleep quality had a significantly increased risk of osteoporosis (ELSA: HR = 1.89, 95% CI: 1.47–2.44; HRS: HR = 1.52, 95% CI: 1.26–1.82).ConclusionPoor sleep trajectories significantly increase osteoporosis risk, suggesting sleep improvement may help prevent bone loss. These consistent findings across two cohorts support sleep-focused interventions as a potential osteoporosis prevention strategy.